2013
DOI: 10.1371/journal.pone.0056641
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic Differentiation Capacity of Human Skeletal Muscle-Derived Progenitor Cells

Abstract: Heterotopic ossification (HO) is defined as the formation of ectopic bone in soft tissue outside the skeletal tissue. HO is thought to result from aberrant differentiation of osteogenic progenitors within skeletal muscle. However, the precise origin of HO is still unclear. Skeletal muscle contains two kinds of progenitor cells, myogenic progenitors and mesenchymal progenitors. Myogenic and mesenchymal progenitors in human skeletal muscle can be identified as CD56+ and PDGFRα+ cells, respectively. The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 53 publications
6
94
0
Order By: Relevance
“…However, the process for the spontaneous phenotypic differentiation of MSCs into osteoprogenitor cells or osteoblasts has not been clearly elucidated. Some authors suggest that miRNA and epigenetic alterations regulate osteogenic differentiation of progenitor cells in muscle sites and in vitro [23,24]. We, too, hypothesize that genetic and epigenetics aspects are major factors controlling lineage commitment of MSCs.…”
Section: Discussionmentioning
confidence: 84%
“…However, the process for the spontaneous phenotypic differentiation of MSCs into osteoprogenitor cells or osteoblasts has not been clearly elucidated. Some authors suggest that miRNA and epigenetic alterations regulate osteogenic differentiation of progenitor cells in muscle sites and in vitro [23,24]. We, too, hypothesize that genetic and epigenetics aspects are major factors controlling lineage commitment of MSCs.…”
Section: Discussionmentioning
confidence: 84%
“…In muscles from HDs, a subpopulation of CD90 -MSCs is reportedly capable of differentiating into osteoblasts, adipocytes, and chondrocytes under appropriate conditions in contrast to CD90 + MSCs, which have limited adipogenic and chondrogenic differentiation potential (21). PDGFRα + cells, which exhibited an in vitro and in vivo osteogenic differentiation potential in normal muscles, have been observed on histological sections proximal to the HO-muscle interface in one trauma patient (18). In our study, patient-derived NHO-MDSCs expressed the classical CD73, CD105, and CD90 mesenchymal markers, and, similar to BM-MSCs, they could differentiate toward osteogenic and adipogenic lineages.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, Tie2 + P-DGFRα + Sca-1 + progenitors that reside in the murine skeletal muscle interstitium generated ectopic bone in a similar BMP-2-dependent model of HO (17). Osteogenic differentiation capacity of PDGFRα + cells isolated from healthy human skeletal muscles was confirmed in vivo when they were implanted subcutaneously on hydroxyapatite scaffolds (18). A third possible source of precursors is a cell population with a CD73 + CD105 + CD90 + MSC phenotype, capable of in vitro adipogenic, osteogenic, and chondrogenic (AOC) differentiation, which was isolated from combat-injured muscle from wounded military personnel; however, there is no functional in vivo study to prove that these cells were at the origin of combat injury-induced HOs (19).…”
Section: Introductionmentioning
confidence: 89%
“…Two types of mesenchymal progenitor cells were found locally in the muscles: satellite cells and interstitial cells [100]. In the series of experiment we have shown that muscle interstitial to regenerate myofibers in vivo following muscle injury [100,278], were all capable of osteogenic differentiation in vitro as previously reported in mouse [109] and human [250].…”
Section: Chapter 8: General Conclusionsupporting
confidence: 77%
“…Although this remains to be demonstrated genetically with lineage tracking experiments, muscle satellite cell, interstitial cells or MPCs sorted from the muscle of naïve mice, which all have the potential to regenerate myofibers in vivo following muscle injury [101], were all capable of osteogenic differentiation in vitro as previously reported in mouse [109] and human [250]. It has been proposed that substance P might be one of systemic factors responsible for HO in mouse models of FOP [36,126].…”
Section: Sca1mentioning
confidence: 70%